Quarantine Due to the COVID-19 Pandemic From the Perspective of Pediatric Patients With Type 1 Diabetes: A Web-Based Survey - Passanisi, Stefano; Pecoraro, Maria; Pira, Francesco; Alibrandi, Angela; Donia, Vittoria; Lonia, Paola; Pajno, Giovanni Battista; Salzano, Giuseppina; Lombardo, Fortunato (Frontiers in Pediatrics, 2020)
Background. A crucial aspect of the 2019 coronavirus disease (COVID-19) pandemic was the psychological impact on the population. Most countries issued restrictive laws to reduce community-based viral spread. Children and adolescents were forced to experience physical and social distancing. Subjects with chronic diseases, such as type 1 diabetes, were more vulnerable and at higher risk of developing psychological disorders. Methods. We conducted a web-based survey to investigate the behavioral responses during quarantine due to the COVID-19 outbreak in a cohort of pediatric patients with type 1 diabetes. Data were collected on demographic and clinical characteristics, lifestyle changes, and the impact of COVID-19 on the management of diabetes. Results. Two hundred four pediatric patients (aged 5-18 years) with type 1 diabetes completed the questionnaire. Interestingly, patients ≤12 years were significantly more influenced by the quarantine period in their approach to the disease than older patients. Conclusion. Although quarantine was a stressful psychological condition, our results showed that most children and adolescents with type 1 diabetes developed high levels of resilience and excellent coping skills by using technology in a proper way.